EXPERIMENTAL STUDY OF THE SYSTEM MAXIMA EFFICIENCY AS A TOOL FOR OPERATIONS RESEARCH TRAINING OF COMPUTER SCIENCE BACHELORS - Kogut, У.П. (Journal of Information Technologies in Education (ITE), 2015)
In the emerging information society, the role of training highly skilled professionals who are capable of productive activity in this society. Therefore, an important task is to develop ICT competencies that would provide an opportunity to resolve personal and professional tasks in conditions of intensive development of modern technologies. Training Operations Research needs special attention, for combining both fundamental concepts and principles of various informatychnyh disciplines and applied models and algorithms for their application. Characteristics of modern information and communication technologies is an essential condition for the capture of all education, including informatychnymy, disciplines, forming a scientific outlook, holistic scientific world. Therefore there is the need to identify ways of using ICT in teaching computer science bachelors operations research in the pedagogical universities,modernizing the learning environment based on trends of science and technology, improving methodical system of education, particularly through the use of computer mathematics as a means of education. This article analyzes the experimental study of the effectiveness of using the system Maxima in learning computer science bachelors operations research. The article outlines the directions pedagogical use of computer mathematics (CKM) when studying operations research and identify methodological aspects of these systems in teaching this course as an example SCM Maxima.